PERANCANGAN APLIKASI CHORD UKULELE BERBASIS ANDROID MENGGUNAKAN ALGORITMA TURBO BOYER MOORE - Purba, Sry Asliza Br (STMIK Budi Darma, 2017)
Ukulele includes a portable instrument that is easy to carry anywhere because of its small size. In playing ukulele certainly not apart from the chord. Chord better known as